2007
DOI: 10.1111/j.1365-2656.2006.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

The extended Moran effect and large‐scale synchronous fluctuations in the size of great tit and blue tit populations

Abstract: Summary1. Synchronous fluctuations of geographically separated populations are in general explained by the Moran effect, i.e. a common influence on the local population dynamics of environmental variables that are correlated in space. Empirical support for such a Moran effect has been difficult to provide, mainly due to problems separating out effects of local population dynamics, demographic stochasticity and dispersal that also influence the spatial scaling of population processes. Here we generalize the Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 58 publications
4
81
1
Order By: Relevance
“…Accordingly, both species have been used as model systems in studies examining a range of issues including nest site selection (Slagsvold, 1975), the role of nestbox design in determining reproductive parameters (Karlsson and Nilsson, 1977;Lambrechts et al, 2010;Møller et al, 2014a) and host-parasite interactions (Hebda et al, 2013). Meanwhile, other studies have examined temporal (Visser et al, 1998(Visser et al, , 2006 and spatial variation in their reproductive parameters (Visser et al, 2003;Møller et al, 2014b) and as large proportions of birds occupy nestboxes, then other studies have examined their population dynamics (Kluijver, 1951;Saether et al, 2007).…”
Section: Blue Tits and Great Titsmentioning
confidence: 99%
“…Accordingly, both species have been used as model systems in studies examining a range of issues including nest site selection (Slagsvold, 1975), the role of nestbox design in determining reproductive parameters (Karlsson and Nilsson, 1977;Lambrechts et al, 2010;Møller et al, 2014a) and host-parasite interactions (Hebda et al, 2013). Meanwhile, other studies have examined temporal (Visser et al, 1998(Visser et al, , 2006 and spatial variation in their reproductive parameters (Visser et al, 2003;Møller et al, 2014b) and as large proportions of birds occupy nestboxes, then other studies have examined their population dynamics (Kluijver, 1951;Saether et al, 2007).…”
Section: Blue Tits and Great Titsmentioning
confidence: 99%
“…More far-reaching consequences may be expected if such climate-enforced synchronization acts on the level of ecological communities (7,8). However, linking cross-species synchrony to common environmental drivers has proven difficult as variation among species in the form of density regulation and response to other environmental drivers often has a desynchronizing effect (9). Thus, observed synchrony usually results from trophic interactions, such as the cofluctuations among predators because of shared prey (3).…”
mentioning
confidence: 99%
“…Aphid populations in the United Kingdom exhibited correlated dynamics at scales of 350-400km, owing to the broad scales at which the NAO influenced their dynamics (Saldana et al 2007). Saether et al (2007) reported that the spatial scale of correlation differed between populations of two common European birds: the great tit, Parus major, and the blue tit, Cyanistes caeruleus, partly due to the scale of the environmental forces acting on each population. Spatial correlations among blue tit populations declined substantially at scales >100km whereas great tit populations showed a high degree of coherence across the entire study range (800km) suggesting a more widespread environmental component influencing fluctuations of great tit populations than for blue tit populations (Figure 1.2).…”
Section: List Ofmentioning
confidence: 99%